TINJAUAN HUKUM EKONOMI ISLAM PADA STRATEGI PEMASARAN PRODUK KESEHATAN PT. HERBA PENAWAR ALWAHIDA INDONESIA (Studi Kasus di Stockis HPAI Genteng) - Nasrulloh, M. Alaika; Fikri, Muhammad Kanzul; Pratiwi, Diyah Ayu; Aini, Aula Izatul (Jurnal Ekonomi Syariah Darussalam, 2021)
This thesis aims to find out how the marketing strategy for health products at PT. Indonesian Alwahida Penawar Herb Stockist in a Gentile stockist and know how to review Islamic economic law in the marketing strategy of the company. The type used in this study is descriptive analysis, which describes the data that researchers collect both from observations, interviews and documentation. Data analysis uses interactive model analysis techniques. Research results namely The strategy used by HPAI stockists is a strategy that uses Sharia MLM. The marketing strategy undertaken by HPAI stockists also does not contradict Islamic economic law, which is seen from the absence of conflicting provisions on animals No: 75 / DSN-MUI / VII / 2009 concerning Sharia Tiered Direct Sales (PLBS).